Atributos do solo, fisiologia, produção e qualidade do maracujazeiro amarelo sob irrigação, redução de perdas hídricas e matéria orgânica - Souza, José Thyago Aires (2019)
In cultivation of yellow passion fruit, the reduction in water application and losses is increasingly essential, has seen the depletion of the world hydric volume in quantity and quality, that associated with the use of organic inputs can help in maintaining the dynamics of edaphic attributes, development of plants, physiological aspects, production potential and fruit quality in the evaluated crops. In this context, an experiment was carried out during the period from November/2016 to October/2017 Remígio municipality , Paraiba State, Brazil, in order to evaluate the effects of irrigation depths reduction from 100 to 60% of evapotranspiration of culture and water losses on soil treated with doses of bovine manure on soil attributes, physiological aspects of plants, plants production and physic-chemical quality of Yellow Giant BRS passion fruit (BRS GA1).The experimental design was a randomized block with subdivided plot, with three replicates, using the factorial scheme 2 × (2 × 5), referring to irrigation depths of 60 and 100% of crop evatranspiration–ETc, pits without and with lateral protectionwith plastic film to reduce soil water losses by lateral infiltrationand doses of 0.0; 2.5; 5.0; 7.5 and 10.0 L of bovine manure per pit.The irrigation depths corresponded to the main plot and the combination between lateral protection of the pits and the doses of organic matter to the subplots. Increasing the dose of bovine manure stimulated the accumulation of nutrients, P, K+, Ca2+, Mg2+, Na+, Beyond the pH, organic matter content, sum of bases, cation exchange capacity, base saturation percentage and humidity, attenuating the temperature in the edaphic environment, especially us irrigated treatments when based on 100% of Etc. The association of bigger irrigation depth with the largest doses of organic matter promoted an increase in indexes of chlorophyll a, b and total, stomatal conductance, internal carbon concentration, photosynthetic, transpiratory rate, instantaneous carboxylation efficiency, production components and physical-chemical quality of fruits. The lateral lining of the pits did not influence in the edaphic attributes, except the organic matter content, but raised humidity and reduced the soil temperature, irrespective of the irrigation depth used. Despite the lateral protection of the pits with plastic film have influenced positively the stomatal conductance, the internal carbon dioxide concentration of the plant sand the average mass of the fruits did not increase the productivity of the crop.